SIMBOL-SIMBOL RELIGIUS KATOLIK DALAM MISA ARWAH (REQUIEM) (ANALISIS SEMIOTIK) - PONDAAG, PRISILIA AMBROSIA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT Â This study entitles â€œSimbol-simbol Religius Katolik Dalam Misa Requiem: Analisis Semiotikâ€. A symbol is a sign that shows the natural relationship between signifier and signified. The relationship between signifier and signified is an arbitrary and it is based on the convention (deal) of society. The religious symbol distinguished from other symbols. It is a representation of something that totally exist outside the conceptually. Religious symbol refers to the ultimate reality that is implicit in religious acts, to what concerns us in the end. Â This study is an attempt to identify, classify, and analyze the religious symbol in requiem mass by the Catholics. The data are collected through the writerâ€™s experience which follow the whole of requiem mass and based on the order of requiem mass bookâ€™s. The writer uses the theory of John Riches in Dillistone to identify, classify, and analyze the data as symbol which states that religious symbol is a symbol that related to the special community or inside the certain communities. The writer uses a descriptive method of Nazir. The results of this study show that based on the theory of Dillistone, there are four kinds of religious symbol in requiem mass. Those are, the symbols that reveal to the general visual of God, the symbols that reveal to the general visual of human, the symbols that reveal to the general visual of world, and the symbols that reveal to the general visual of reality. The meaning of religious symbol in requiem mass is a way of communicaton among the religious community and God by the symbols that used in a mass such as verbal and non verbal symbol to tell a purpose and pray. Â The writer hopes that this study will help the reader to understand about semiotics especially on symbol as one of many ways to communicate. Keywords: Catholic Religious Symbol, Requiem Mass, Semiotic Analysis.